Indonesia's Open Government: A Bibliometric Analysis - Syed Agung Afandi; Muslim Afandi; Rizki Erdayani; Nail Hidaya Afandi (Journal of Governance and Social Policy, 2023)
This study aims to analyse trends and models of open government in Indonesia. This study uses a qualitative approach with bibliometric analysis methods and a systematic literature review. The data in this study were obtained from the Google Scholar database using the Publish or Perish application and processed using the Vosviewer application. The results of this study indicate that Indonesian open government studies are quite attractive to researchers. Although fluctuating, in the last decade there have been 52 publications on Indonesian open government studies, and 267 of them have been cited. From these figures, an h-index score of 10 and a g-index score of 15 are obtained. There are 83 keywords divided into 15 clusters, with the number of keywords in each cluster varying. Of these keywords, there are 412 links, 440 total link strength, and 132 occurrences. In 2020–2022, the Government of Indonesia established 18 policy models to support the achievement of open government. Since 2011 until now, the government of Indonesia has consistently supported the implementation of open government by establishing 152 policy models.